Low-temperature ¹Н NМR spectroscopic study of hydration properties of a hybrid system based on nanosilica, DNA and doxorubicin in the presence of C₆₀ fullerene - Turov, V.V.; Prylutskyy, Yu.I.; Ugnivenko, A.P.; Barvinchenko, V.N.; Krupskaya, T.V.; Tsierkezos, N.G.; Ritter, U. (Физика низких температур, 2014)
The structure of hydrate cover layers of SiO₂–DNA–Dox (where Dox: doxorubicin) and SiO₂–DNA–Dox–C₆₀ fullerene hybrids was studied by means of low-temperature ¹H NMR spectroscopy in tetrachloromethane. The hydration properties of SiO₂–DNA–Dox nanomaterials combined with fullerenes and their derivatives are extremely important for their further use as therapeutics in cancer treatment and for safety reasons. The findings reveal that the hydration properties of the hybrids differ from those of the solid DNA particulates or SiO₂–DNA systems due to the existence of different types of water clusters, namely the weakly- (WAW) and stronglyassociated water (SAW) clusters. For SAW clusters the radial distributions as well as the distributions of change in Gibbs free energy due to adsorptive interactions at the surfaces of the investigated systems were obtained.